Mikroelementy w pokopalnianych gruntach w rejonie Łęknicy = Microelements in the post-mining grounds in Łęknica region - Greinert, Henryk; Greinert, Andrzej; Drab, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper were introduced changes of microelements content in the post-mining grounds in Łęknica region. The content of microelements in described ground material was very low (Mn < 10,2, Cu < 1,8, Zn < 6,4, Ni < 3,2, Co < 2,3, Pb < 8,2 mg?kg-1). After use of magnesium lime from zinc mill the change of content of Mn, Zn, Cu and Pb in grounds was noticed. In the samples, taken after 20 years of forest reclamation, the largest content of microelements in duff has been noted (Mn 31,9-57,4, Cu 6,3-20,4, Zn 100,9-105,5, Ni 6,3-8,9, Co 1,7-2,8, Pb 12,8-31,0 mg?kg-1). Decrease of content with ground depth was clearly observed.
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); rekultywacja; zwałowiska pokopalniane; mikroelementy; forest reclamation; post-mining dumps; microelements